Theoretical investigation of a positron binding to an aspartame molecule using the ab initio multicomponent molecular orbital approach. Issue 17 (21st February 2014) - Oba, Yuki; Tachikawa, Masanori; Brändas, Erkki; Szabados, Ágnes; Surján, Péter
<x xml:space="preserve">Abstract</x> The feature of positron binding to aspartame molecule was analyzed using the ab initio multicomponent molecular orbital method. All nine stable conformers for aspartame molecule have positive positron affinity (the binding energy of a positron) values, which means that a positron can be attached to parent aspartame molecule. Analyzing the positronic orbitals of positronic aspartame conformers and the electrostatic potential maps of the corresponding parent molecules, we found that long‐range electrostatic interaction is the most crucial role in positron binding to aspartame molecule. We theoretically confirmed the possibility of positron binding to the conformers of aspartame molecule with strong dipole moment. © 2014 Wiley Periodicals, Inc.